2021
DOI: 10.2478/hukin-2021-0090
|View full text |Cite
|
Sign up to set email alerts
|

Age and Maturity Effects on Morphological and Physical Performance Measures of Adolescent Judo Athletes

Abstract: Studies assessing age and maturation effects on morphological and physical performance measures of young judokas are scarce. This study aimed to assess the independent and combined effects of chronological age and biological maturation on anthropometry and physical performance of 67 judokas aged 11-14. Participants’ anthropometric profiles were assessed, and physical performance tests were completed. Multivariate analyses of variance revealed an independent effect of age (anthropometry: F = 1.871; p < 0.05;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Indeed, biological maturation does not take place at the same time for all individuals ( Lloyd et al, 2014 ). This effect of maturity has shown its influence on the evolution of the performance of young athletes in different sports such as judo Giudicelli et al (2021) , football ( Peña-González et al, 2022 ), rowing} ( Thiele et al, 2021 ) and basketball ( Torres-Unda et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, biological maturation does not take place at the same time for all individuals ( Lloyd et al, 2014 ). This effect of maturity has shown its influence on the evolution of the performance of young athletes in different sports such as judo Giudicelli et al (2021) , football ( Peña-González et al, 2022 ), rowing} ( Thiele et al, 2021 ) and basketball ( Torres-Unda et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…When youth athletes are exposed to numerous hours of deliberate practice without understanding the training context and having a precise aim will not lead to the desired effects in training or competitions [ 54 ]. However, the maturation effect on growth and physical performance in young judokas has been highlighted as it seems more relevant than the age effect [ 55 , 56 ]. Additionally, it has been shown that maturation attenuated the age effect and significantly affected upper body and handgrip strength in youth judokas [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Biological maturation is significantly related to youthful growth and physical performance (Giudicelli et al, 2021;Luna-Villouta et al, 2021). Of the six studies included in this systematic review, two studies attempt to show the relationship between maturity and physical performance.…”
Section: Maturity and Growthmentioning
confidence: 99%